The Großschwabhausen binary survey1. Issue 1 (15th February 2017) - Mugrauer, M.; Buder, S.; Reum, F.; Birth, A.
Abstract : Background: Since 2009, the Großschwabhausen binary survey is being carried out at the University Observatory Jena. This new imaging survey uses available time slots during photometric monitoring campaigns, caused by nonphotometric weather conditions, which often exhibit good atmospheric seeing. The goal of the project is to obtain current relative astrometric measurements of the binary systems that are listed in the Washington Visual Double Star Catalog. Materials and Methods: For the survey we use the Refraktor‐Teleskop‐Kamera at the University Observatory Jena to take imaging data of selected visual binary systems. Results: In this paper, we characterize the target sample of the survey, describe the imaging observations and the astrometric measurements including the astrometric calibration, and present the relative astrometric measures of 352 binaries that could be obtained during the course of the Großschwabhausen binary survey, so far.